Comprehensive Evaluation of a Landscape Fabric Based Solar Air Heater in a Pig Nursery - Li Yu (MDPI AG, 2021)
Supplementing fossil fuels with solar air tempering for brooding young livestock could reduce energy use and improve indoor air quality. Metal transpired solar collectors (TSC) are effective but too expensive for heating livestock buildings. An inexpensive 12.7 m2 dark grey landscape-fabric-based transpired solar collector (fTSC) was evaluated in a swine nursery with two herds of pigs. A fraction of the fTSC area was underlain with phase change material (PCM) to store excess heat. The Test room with the fTSC was compared with an adjacent identical Control room, each with 120 piglets. The fTSC provided supplemental heating, e.g., with a suction velocity (Vs) of 0.027 m/s during a 9 h period, air temperature was increased by 11.6 °C (mean irradiance of 592 W/m2). Between 4 pm and 9 pm that same day, the PCM increased air temperature by 3.9 °C. The fTSC did not reduce propane use or improve pig performance. Higher Vs, operational changes and controller modifications could improve system performance and reduce cost. Modeling could be used to optimize PCM use. Hence, this very low-cost fabric-based solar air heater offers potential for considerable reduction in heat energy use in livestock barns.